FITUR-FITUR TUTURAN YANG DIGUNAKAN MARGARET THATCHER DALAM WAWANCARA TV - WAHYUNI, DELVA ([Yogyakarta] : Universitas Gadjah Mada, 2015)
The study is entitled speech features used by Margaret Tatcher in the TV interviews. The aims of this study are to describe types of the women speech features, to describe the functions of women speech features and to describe men speech features used by Margaret Thatcher as she is known by Iron Lady. This research is descriptive qualitative research. In collecting data, this study uses note taking technique. The data of this research are taken from the transcript of the film then sorted based on the use of women speech features. Then the data are analyzed using a the theory of women speech features by Lakoff (1975). The function of women speech features is described by Lakoff's theory, and men speech features used by Margaret Thatcher is explained by theory of Coates. The results of the data analysis are presented using informal method by using the ordinary word. The findings show that 1) Margaret Thatcher used nine of women speech features, i.e. âlexical hedgesâ, âtag questionsâ, ârising intonation on declarativesâ, âempty adjetivesâ, âprecise color termsâ, âintensifiersâ, âsuperpolite formsâ, âavoidance of strong swear wordsâ and âemphatic stressâ, 2) the functions of women speech features consist of weaken the strength of an assertion function (hedging devices), i.e. lexical hedges, tag questions, rising intonation on declaratives, superpolite forms and strengthen the strength of an assertion (boosting devices), i.e. âintensifierâ, âemphatic stressâ, âempty adjectiveâ, and âprecise color termsâ , 3) Margaret Thatcher used men speech features as she is known by Iron Lady, i.e. direct forms and (soft) swear words. Keywords: Women Speech Features, Margaret Thatcher, TV Interviews Language and Gender, Women Language